The Effect of Profitability and Leverage on Islamic Social Reporting Disclosure with Company Size as a Moderating Variable - Fitri, Tia Nur; Syarief, Mochamad Edman (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
This study examines the effect of profitability and leverage on Islamic social disclosure with company size as a moderating variable in companies listed on IDX-MESBUMN17 in 2018-2023. This study uses the EViews 12 application as an analysis tool. The analysis method used is moderated regression analysis (MRA). By using the purposive sampling method, 14 companies listed on IDX-MESBUMN17 were obtained. The random effect model (REM) is the most appropriate estimate for this model. The results of the study indicate that leverage affects the disclosure of Islamic social reporting, while profitability does not affect Islamic social disclosure. The results of the moderation test show that only leverage is moderated by company size in disclosing Islamic social reporting; profitability cannot be moderated by company size in disclosing Islamic social reporting.